Effectiveness of hCMV, mEF1a and mAct promoters on driving of foreign gene expression in transgenic zebrafish - . Alimuddin; G. Yoshizaki; O. Carman; T. Takeuchi (Jurnal Akuakultur Indonesia)
Highly unsaturated fatty acids (HUFA), especially eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) have long been recognized for its beneficial effect for human health and development.   The D6 fatty acid desaturase is generally considered to be the rate-limiting factor in HUFA biosynthesis.  Here, as the first step of study, we conducted experiment to select an appropriate construct that allows higher expression levels of masu salmon (Oncorhynchus masou) D6-desaturase gene in zebrafish (Danio rerio) in order to increase its activity for synthesizing EPA/DHA.  Salmon D6-desaturase cDNA (sD6) was separately ligated with human cytomegalovirus (hCMV), medaka elongation factor 1a (mEF1a) and medaka b-actin (mAct) promoters.  The resulted construct was designated as hCMV-sD6, mEF1a-sD6 and mAct-sD6, respectively.  Each of the constructs in circular DNA form was microinjected into 1-cell stage embryos at a concentration of 30mg/ml. Transgenic individuals were identified by polymerase chain reaction (PCR) and their expression levels were analyzed by reverse transcription PCR.  The first (F1) and second (F2) generation was produced by crossing the transgenic founder F0 and F1, respectively, with wild-type fish.  The results showed that the highest transient gene expression level was obtained from the mAct-D6 construct, followed respectively by EF1a-D6 and hCMV-D6 construct. The transmission rate of transgene into F1 generation was 4.2%-44.1%, and into F2 was followed the Mendellian segregation pattern.   Expression of transgene in F2 generation was varied between strains regarding as the mosaics of F0 fish.  Now, a transgenic system to study the modification of fatty acid biosynthesis pathways in fish was established.  Further investigations are to produce fish containing higher levels of EPA and DHA.